Migrating merchants: trade, nation, and religion in seventeenth-century Hamburg and Portugal - Poettering, Jorun (De Gruyter Oldenbourg, 2019)
What impact did the cultural origins and religious backgrounds of the merchants in the early modern period have on their business activities? How did these people manage to integrate themselves into the foreign societies within which they lived and worked? In this book Jorun Poettering examines the circumstances of the merchants who traded between Hamburg and Portugal in the seventeenth century. Her study offers new insights into the history of migration and intercultural encounter as world became more interconnected.